1994
DOI: 10.1002/ajmg.1320490417
|View full text |Cite
|
Sign up to set email alerts
|

X‐linked laterality sequence in a family with carrier manifestations

Abstract: X-linked laterality sequence (XLLS) consists of situs inversus, complex cardiac defects, and alterations in the development of the spleen. We describe a family in which two male cousins had XLLS with caudal manifestations. In our family, the obligate carrier females had uterine septum and hypertelorism, which may be gene carrier manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…The preferential association of asplenialpolysplenia not only with defects of normal body asymmetry (dextrocardia, situs inversus totalis, and situs viscerum inversus), but also with other midline defects. Our present results, together with others from the literature, also support this statement, since polysplenia is observed not only in association with abdominal anomalies and situs inversus (defects that are considered the hallmark of the laterality sequences [Mikkila et al, 1994]), but also with other midline malformations. In this sense, the ECEMC case, published by Salvador et al [19831 (which is included in the present analysis as case number ll), had polysplenia and caudal dysgenesis, as did the two sibs published by Fullana et al [19861 with asplenia.…”
Section: Alteration Of Normal Body Asymmetrysupporting
confidence: 92%
See 1 more Smart Citation
“…The preferential association of asplenialpolysplenia not only with defects of normal body asymmetry (dextrocardia, situs inversus totalis, and situs viscerum inversus), but also with other midline defects. Our present results, together with others from the literature, also support this statement, since polysplenia is observed not only in association with abdominal anomalies and situs inversus (defects that are considered the hallmark of the laterality sequences [Mikkila et al, 1994]), but also with other midline malformations. In this sense, the ECEMC case, published by Salvador et al [19831 (which is included in the present analysis as case number ll), had polysplenia and caudal dysgenesis, as did the two sibs published by Fullana et al [19861 with asplenia.…”
Section: Alteration Of Normal Body Asymmetrysupporting
confidence: 92%
“…One of the cases described by Peoples et al [19831 Toriello et al [1986] cited previously reported cases who presented with encephalocele, anophthalmia, and diaphragmatic hernia. In the family described by Mikkila et al [1994], in which polysplenia was also associated with caudal dysgenesis, one of the individuals had diaphragmatic hernia, although these authors did not consider it as part of the clinical expression of the condition, in spite of that it was also previously observed by Majewski [quoted in Toriello et al, 19861, as well as in one of the cases described by Fullana et al [19861. We found that only one of the 20 cases with polysplenia (Table 111) had bilobed lungs and congenital heart defects (that are part of a so-called laterality sequence), without any other associated anomalies. The other cases, in addition to those defects that are part of the alteration of the normal body asymmetry, have other anomalies such as diaphragmatic and intestinal defects, cranio-facial malformations, central nervous system anomalies, and caudal dysgenesis defects.…”
Section: Alteration Of Normal Body Asymmetrymentioning
confidence: 67%
“…Errors in movement can lead to asplenia or polysplenia [Opitz, 1985], visceral situs inversus, and heart defects. Other possible anomalies include bilateral bilobed or trilobed lungs, midline liver, bowel atresia or malrotation, annular pancreas [Iuchtman et al, 1993], renal malformations [Mikkilä et al, 1994], and sacral hypoplasia. Total situs inversus-or mirror-image reversal-may be clinically different from other forms of heterotaxia, but either can result from the same abnormal allele in some families [Mathias et al, 1987].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 A submicroscopic deletion in Xq26 associated with familial situs ambiguous has been reported. 12 Casey et al reported that familial situs abnormalities were linked to a gene at Xq24-q27.…”
Section: Discussionmentioning
confidence: 99%